Unsymmetrically coordinated single Fe-N3S1 sites mimic the function of peroxidase. (October 2021) - Jiao, Lei; Kang, Yikun; Chen, Yifeng; Wu, Nannan; Wu, Yu; Xu, Weiqing; Wei, Xiaoqian; Wang, Hengjia; Gu, Wenling; Zheng, Lirong; Song, Weiyu; Zhu, Chengzhou
Highlights: Unsymmetrically coordinated Fe-N3 S1 as active sites in single-atom catalysts are successfully constructed. Fe-N3 S1 sites exhibit higher peroxidase-like activity than Fe-N4 sites. Fe-N3 S1 sites lengthen the OO bonding distances of adsorbed H2 O2 and accelerate the electronic transfer between Fe and O. A colorimetric biosensor for the detection of organophosphorus pesticides is established. Graphical Abstract: ga1 Abstract: The development of highly active biomimetic catalysts with peroxidase (POD)-like activity and realization of vivid mimicking of the active sites of natural enzymes still remains a huge challenge. Herein, atomically dispersed Fe atoms on hierarchically S/N co-doped porous carbon (FeSNC) featured with the unsymmetrically coordinated Fe-N3 S1 as active sites were synthesized by a template-assisted method. The resultant FeSNC exhibits higher POD-like activity than FeNC featured with Fe-N4 sites. Owing to the S doping-induced geometric/electronic effects, Fe-N3 S1 not only lengthens the OO bonding distances of adsorbed H2 O2 but also accelerates the electronic transfer between Fe and O, decreasing the energy barrier of the formation of the active intermediate and thus achieving the boosted POD-like activity. Finally, the sensitive detection of organophosphorus pesticides was performed by adjusting the POD-like activity of FeSNC, exhibiting satisfactory sensitivity and selectivity. This work provides great promise for the accurate design of single-atom catalysts for vivid mimicking the function of natural enzymes.